Selection of Suitable Potato Genotypes for Late-Sown Heat Stress Conditions Based on Field Performance and Stress Tolerance Indices - Al Mahmud, A.; Alam, M.J.; Kundu, B.C.; Skalicky, M.; Rahman, M.M.; Rahaman, E.H.M.S.; Sultana, M.; Molla, M.S.H. (MDPI, 2021)
International Potato Center (CIP), -bred potato genotypes produce various yields under heat stress conditions due to being sown late. To explore options for achieving this, a replicated experiment was conducted at the field of Tuber Crops Research Sub-Centre, Bangladesh Agricultural Research Institute, Bogura, Bangladesh to evaluate the performance of fourteen CIP-bred potato genotypes with two controls (Asterix and Granola). The experiment was laid out in a split-plot design with three replications. Several indices were applied to find out the suitable genotypes under heat stress. The plant height increased by 34.61% under heat stress, which was common in all the potato genotypes. Similarly, other yield-participating characters like stem per hill, canopy coverage (%), plant vigor, and tuber number per plant were also increased under heat stress conditions. However, the tuber yield was decreased by 6.30% and 11.41%, respectively when harvested at 70 and 90 days after plantation. Moreover, "CIP-203" yielded the highest (40.66 t ha(-1)) in non-stressed whereas, "CIP-118" yielded the highest (32.89 t/ha) in stressed conditions. Likewise, the bred "CIP-218" and "CIP-118" performed better under both growing conditions and yielded >35.00 t ha(-1). According to a rank-sum test, among the fourteen potato genotypes, "CIP-218", "LB-7", "CIP-118", "CIP-232", and "CIP-112" were selected as heat-tolerant potatoes and can grow in both growing conditions with higher yield potential.